2020
DOI: 10.1016/j.vas.2020.100127
|View full text |Cite
|
Sign up to set email alerts
|

Performance, blood profile and gut morphometry of broiler chickens fed diets supplemented with Yohimbe (Pausynistalia yohimbe) and Larvacide

Abstract: The need for making livestock products free from antibiotics residue and other synthetic chemicals has resulted to the use of herbal products in livestock production. A 42-day study was conducted to compare the influence of Yohimbe ( Pausynistalia yohimbe) and Larvacide on the growth performance, blood profile and gut morphometry of broiler chickens. Two hundred and twenty five 14-day old broiler chickens were randomly allotted into five treatment groups comprising of forty five chicks e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…An improved nutrient digestibility is concomitant with ME-LP supplement because these probiotics are thought to result in more nutrients becoming available for absorption via the suppression of growth and metabolic activities of the gut pathogens, as well as alterations in intestinal growth, morphology, and function such as reduction of intestinal epithelium thickness and epithelial cell turnover. Moreover, this may probably involve the stimulated secretion of bile, mucus, and endogenous enzymes (trypsin, chymotrypsin, lipase, and amylase) in the pancreas and intestinal wall by probiotic bacteria [ 33 ]. Similarly, the adding of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…An improved nutrient digestibility is concomitant with ME-LP supplement because these probiotics are thought to result in more nutrients becoming available for absorption via the suppression of growth and metabolic activities of the gut pathogens, as well as alterations in intestinal growth, morphology, and function such as reduction of intestinal epithelium thickness and epithelial cell turnover. Moreover, this may probably involve the stimulated secretion of bile, mucus, and endogenous enzymes (trypsin, chymotrypsin, lipase, and amylase) in the pancreas and intestinal wall by probiotic bacteria [ 33 ]. Similarly, the adding of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol, thymol, and limonene at 100 ppm in encapsulated form improved AID of nutrients and growth performance in broilers [ 37 ]. This is possibly due to the stimulated secretion of bile, mucus, and endogenous enzymes (trypsin, chymotrypsin, lipase, and amylase) in pancreas and intestinal wall [ 38 ]. The high CP digestibility in MBO group may enhance bioavailable amino acids and cell proliferation, resulting in increased intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Alagbe [3] Albumin content in the blood are generally influenced by protein shortages, however, the values reorted fall within the range reported by Subhadarsini and Silpa [45]. Ibrahim [46] ; Obajuluwa, et al [55]; Olafadehan, et al [56]; Livingston, et al [57] reported a globulin and uric acid range of (1.6 -1.9 g/dl) and (3.7-5.2 mg/dl) respectively. This result is also in agreement with the findings of Obiakaonu, et al [58] and Simeraks, et al [59].…”
Section: Resultsmentioning
confidence: 53%